Application of AI in manufacturing : constraint networks for concurrent engineering, applied to surface mount technology - Minnaar, Steve(Stephanus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1992.